2007
DOI: 10.1097/dmp.0b013e3181583d66
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Functions of Health Unified Command and Emergency Operations Centers for Large-scale Bioevent Disasters Within the Existing ICS

Abstract: The incident command system provides an organizational structure at the agency, discipline, or jurisdiction level for effectively coordinating response and recovery efforts during most conventional disasters. This structure does not have the capacity or capability to manage the complexities of a large-scale health-related disaster, especially a pandemic, in which unprecedented decisions at every level (eg, surveillance, triage protocols, surge capacity, isolation, quarantine, health care staffing, deployment) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 35 publications
(66 reference statements)
0
64
0
Order By: Relevance
“…The important questions to be answered, therefore, are "who is the appropriate leader for healthcare systems in emergency situations? " and "what are the necessary characteristics for such leaders? "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important questions to be answered, therefore, are "who is the appropriate leader for healthcare systems in emergency situations? " and "what are the necessary characteristics for such leaders? "…”
Section: Introductionmentioning
confidence: 99%
“…International studies have shown a significant gap in disaster commanding requirements, and Iran is no exception. To eliminate the existing barriers and to improve disaster management in Iran, the present study aimed to explore the required characteristics of the operational incident commanders in Iranian health sector.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid recognition, and effective response, to a bioterrorism event requires that clinicians and public health officials work together. [42][43][44] In some circumstances, such as smallpox, the diagnosis of a single case triggers the alarm that a bioterrorism event has occurred. 45 However, for any of the diseases with a naturally occurring incidence, as well as with a novel organism or illness that has not yet been identified, it is the existence of a cluster of cases in a geographic area that triggers suspicion of a possible bioterrorism attack or emerging epidemic ( Table 5).…”
Section: Diagnosismentioning
confidence: 99%
“…HICS (formerly called the Hospital Emergency Incident Command System)'" is an adaptation for hospitals of the incident command system mandated by The Joint Commission; its importance is widely recognized. 45,46 It is not surprising that almost all ED directors had at least heard ofHICS, although the finding that only about half were very conversant with it and that just over half were very familiar with specific roles assigned to ED www.disastermedicinejoumal.com personnel in HICS is disturbing. Similarly, although experiences with both simulated and actual MCls have proven that communication, including communication involving written memoranda, is ahnost universally a weak link in a disaster,47.50 the observation that more than one-third of respondents reported no written agreements with other hospitals is discouraging.…”
Section: (2)mentioning
confidence: 99%